Sistema de indicadores legais para avaliação da gestão de unidades de conservação aplicado à região semiárida do Brasil - Paz, Ronilson José da (2021)
Conservation units are areas legally instituted by the government in order to allow sustainable use and conserve biodiversity. In this sense, this thesis aims to analyze the conservation units located in the semi-arid region of Brazil, selecting a system of legal indicators that may be able to assess the effectiveness of their management, listing the conservation units located in the semi-arid region of Brazil, emphasizing its importance as natural capital, elaborating a system of legal indicators capable of evaluating the effectiveness of the management of protected areas, presenting the system of indicators capable of evaluating the effectiveness of the management of protected areas, developing a procedure that allows to evaluate the effectiveness of the management of conservation units to be applied by the managers, to reinforce the importance of the conservation units for the management of the natural capital contained in the Semi-arid Region of Brazil, and to characterize the existing natural capital in the Semi-Arid Region of Brazil and ecosystem services provided by conservation units, through bibliographic research and current legislation. At the end, it was observed that 252 conservation units were created in all states covering the Semi-Arid Region of Brazil, of which 72 are fully protected and 180 for sustainable use, with the private natural heritage reserve (PNHR) category being the more created (119), however they protect only 0.06% of the semiarid area. The system of legal indicators to evaluate the effectiveness of the management of protected areas, proved to be adequate to evaluate the selected integral protection and sustainable use units. After applying the index developed in this thesis, it was found that the nine conservation units studied, located in the Semi-Arid Region of the State of Paraíba, present poor performances, where the best was in the Vale dos Dinossauros Natural Monument, which reached only 56% efficiency. The results obtained from the application of the indicator system used in this thesis corroborate the hypotheses raised at the beginning of the research that the efficient management of conservation units contributes positively to the protection and conservation of the natural capital contained in the Semi-Arid Region of Brazil, as well as that the use of a system of indicators that makes it possible to assess the effectiveness of the management of protected areas to be applied by managers allows a better assessment of the management of these protected areas. In view of the fragility of the Caatinga Biome, there is an urgent need to increase the reach of public policies to protect their ecosystems.